Theories of political protest and social movements : a multidisciplinary introduction, critique, and synthesis - Opp, Karl-Dieter (Routledge, 2009)
Political protest and social movements are ubiquitous phenomena. This book focuses on various theoretical approaches that aim at explaining them: the theory of collective action, the resource mobilization perspective, political opportunity structure theory, the identity approach, the framing perspective, and the dynamics of contention approach.